2017
DOI: 10.1177/0888406417718251
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues With Consequential Use of the edTPA: Overall and Through a Special Education Lens

Abstract: The purpose of teacher preparation programs is to ensure that teachers are adequately equipped with the necessary knowledge and skills to support the various educational needs of their students. Nevertheless, a call for a uniform process through which teacher candidates can demonstrate their ability to meet their students’ educational needs using authentic learning environments has been called for. To that end, the American Association of College for Teachers Education (AACTE) partnered with the Stanford Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…To an extent, it is not surprising that many special education teacher candidates have struggled with incorporating selfregulation instruction in the aforementioned rubrics. Criticisms of edTPA rubrics include a lack of clear word choice within the rubrics themselves as well as minimal consideration of student learners, especially those who are learning both academic and functional curriculum (Othman et al, 2017). Furthermore, incorporating self-regulated learning to improve student independence, and as a means Planned assessments (including baseline data) and the daily assessment records are aligned to all lesson objectives and provide evidence for monitoring the focus learner's progress toward the learning goal at different points in the learning segment Assessments for the learning goal reflect appropriate levels of challenge and support in light of the focus learner's specific strengths, needs, and lesson objectives The candidate describes plans to involve the focus learner in monitoring his or her own progress in developmentally appropriate ways 2.9…”
Section: Challenges In Teaching Self-regulation Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…To an extent, it is not surprising that many special education teacher candidates have struggled with incorporating selfregulation instruction in the aforementioned rubrics. Criticisms of edTPA rubrics include a lack of clear word choice within the rubrics themselves as well as minimal consideration of student learners, especially those who are learning both academic and functional curriculum (Othman et al, 2017). Furthermore, incorporating self-regulated learning to improve student independence, and as a means Planned assessments (including baseline data) and the daily assessment records are aligned to all lesson objectives and provide evidence for monitoring the focus learner's progress toward the learning goal at different points in the learning segment Assessments for the learning goal reflect appropriate levels of challenge and support in light of the focus learner's specific strengths, needs, and lesson objectives The candidate describes plans to involve the focus learner in monitoring his or her own progress in developmentally appropriate ways 2.9…”
Section: Challenges In Teaching Self-regulation Skillsmentioning
confidence: 99%
“…For example, Martin et al (2003) suggested that in-service teachers can have difficulty deciding how to start teaching components of self-determination (e.g., selfregulation) or may be apprehensive in adjusting their current instructional approaches (e.g., Zimmerman et al, 1996). Similarly, Othman et al (2017) suggested that for teachers serving students with extensive support needs (e.g., multiple disabilities) and who have limited skill sets, successfully embedding self-regulation goals within the required three to five lesson plans submitted as part of the edTPA assessment can be challenging to demonstrate in such a limited time frame.…”
Section: Challenges In Teaching Self-regulation Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational researchers and teacher educators also have raised concerns about the length and complexity of the edTPA handbook; many teacher candidates struggle to comprehend or allocate time toward reviewing the numerous handbook rubrics and prompts needed to earn a passing score on the portfolio (Greenblatt & O’Hara, 2015; Bergstrand Othman et al, 2017). More specifically, the number of written pages and number of required commentaries (i.e., candidate writing on planning, instruction, and assessment) across all three tasks have been found to demand a high level of “writing stamina and style” (Bergstrand Othman et al, 2017, p. 271), placing an emphasis on extensive writing and specific vocabulary for the candidate to document their instructional abilities.…”
mentioning
confidence: 99%
“…Educational researchers and teacher educators also have raised concerns about the length and complexity of the edTPA handbook; many teacher candidates struggle to comprehend or allocate time toward reviewing the numerous handbook rubrics and prompts needed to earn a passing score on the portfolio (Greenblatt & O’Hara, 2015; Bergstrand Othman et al, 2017). More specifically, the number of written pages and number of required commentaries (i.e., candidate writing on planning, instruction, and assessment) across all three tasks have been found to demand a high level of “writing stamina and style” (Bergstrand Othman et al, 2017, p. 271), placing an emphasis on extensive writing and specific vocabulary for the candidate to document their instructional abilities. While Whittaker et al (2018) have stated the “edTPA is designed as an assessment of pedagogy and scorers are trained and monitored to ensure that writing quality does not bias a scoring decision” (p. 9), Greenblatt (2019) asserts the format requires teacher candidates to write on individual components of the teaching process separately (e.g., planning, instruction, and assessment), necessitating the use of both analytical and reflective writing styles.…”
mentioning
confidence: 99%